Three-Dimensional Printing and Computer Navigation for Correction of Multiple Deformities in Osteogenesis Imperfecta: A Case Report. Issue 2 (April 2021) - Chan, Ping-Keung; Fang, Christian; Fang, Evan; Leung, Matthew; Yan, Chun-Hoi; Chiu, Kwong-Yuen
Abstract : Case: A 44-year-old man with osteogenesis imperfecta presented with multiple debilitating musculoskeletal deformities. Bi-level osteotomies, assisted by 3-dimensional (3D)-printed patient-specific cutting guides, were performed to correct extraarticular valgus and procurvatum tibial deformities. Concomitant computer-navigated total knee arthroplasty was performed to restore neutral mechanical alignment. Postoperative x-ray showed good correction of deformities, and 1 year postoperatively, the patient is able to walk unaided with significant resolution of knee pain. Conclusion: 3D-printed osteotomy guides and computer navigation can be instrumental in procedures requiring a high degree of precision. With sufficient training, modern orthopaedic technologies can be implemented by surgeons themselves and combined to facilitate precise and personalized management of challenging conditions.